Scoliosis compensation and postural responses in school girls - Wilczyński, Jacek; Habik, Natalia; Paprocki, Michał Jerzy; Rychter, Paweł; Wilczyński, Igor; Dworakowska, Danuta (Journal of Education, Health and Sport, 2017)
Introduction. The aim of the study was to analyze the relationship between scoliosis compensation and postural responses in school girls. Material and Methods. Spinal testing was carried out using the photogrammetric Moiré method. Based on the angle size of the spinal curvature, scoliosis posture was distinguished: 1-9° and scoliosis: ≥10°. Postural reactions were examined using the ST 310 Plus Stability System, Tecnobody platform. Results. There were 21 (75%) children with scoliotic posture and 7 (25%) with scoliosis (25%). In primary spinal clavicular, both during tests with open and closed eyes, there were significant direct proportional correlations between clavicular and postural responses. Higher values of clavicular variables were accompanied by increased postural responses. In secondary claviculars, both during tests conducted with open and closed eyes, there were significant but inversely proportional correlations between scoliotic variables and postural responses. Higher values of the sclerotic variables were accompanied by a decrease in postural responses. Conclusion. In compensated scoliosis, by alignment of primary and secondary claviculars, lower postural amplitudes of postural responses were observed. Scoliosis therapy should be directed towards the correction of the primary deflection. Levelling secondary deflections must be subordinated to this. Reducing secondary deflections without simultaneous compensation of the primary deflections is detrimental.